English-Only Policies in Asian Classrooms: A Systematic Review of Effects on Student English Proficiency and Learning Experiences - Luna, Catherine; Tiago, Bhenylouh; Dalope, Raven Sean; Budong, Alexander; Pelila, John Rey (Journal of Multidisciplinary Research and Development, 2026)
Although English-Only Policies (EOP) are widely implemented across Asian education systems, research examining their effects on students’ English proficiency and learning experiences remains fragmented, particularly in multilingual classroom contexts. This study investigates both the positive and negative impacts of EOP on students’ English skills and academic engagement through a systematic literature review. A total of 22 peer-reviewed studies published between 2020 and 2025 in Asian contexts were analyzed using thematic analysis to identify patterns in policy implementation, pedagogical practices, outcomes, and challenges. The findings indicate that nine studies report primarily positive effects of EOP, five report predominantly negative effects, and eight document mixed outcomes. Positive results include improvements in listening, speaking, reading, and writing skills, as well as increased motivation and engagement, particularly when teachers are adequately trained, instructional practices are flexible, and the strategic use of learners’ first language is permitted. On the other hand, rigid or poorly supported EOP implementation is associated with increased learner stress, reduced participation, and negative effects on academic confidence, especially among students with lower English proficiency. In conclusion, the effectiveness of EOP is highly context-dependent and shaped by institutional support, teacher readiness, and classroom practices. Future research could complement existing studies by incorporating experimental, mixed-methods, and longitudinal designs to better examine causal relationships and support evidence-based, context-sensitive policy implementation.